Tingkat Risiko Diabetes Mellitus Tipe 2 Pada Dewasa Berdasarkan Faktor Risiko Yang Dapat Dimodifikasi - Dewanti, Nisa; Diana, Meli; Riesmiyatiningdyah, Riesmiyatiningdyah; Rohmawati, Nina Rizka (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: This study aims to identify the relationship between anthropometric, lifestyle, and high-fibre diet with the risk level of diabetes mellitus type 2 Methods: This article is quantitative study that describes the relationship between modifiable risk factors for diabetes mellitus consisting of body mass index, waist circumference, physical activity level, vegetable eating habit, and exercise habit with the risk factors of diabetes mellitus in adult. The instruments that used ini this study include demographyc questionnaires, Food Frequency Questionnaire (FFQ), and Finish Diabetes Risk Factors (FINDRICS). Data analysus in this study used Chi-Square Correlation Test. Results: Body Mass Index (BMI) showed very significant relationship with the risk of diabetes (P=0.001), high-fiber diet variables showed significant relationship with the risk of diabetes (p=0.01), physical activity had significant ralationship with risk of diabetes (p=0.003, and exercise habit had significant relationship with risk of diabetes (p=0.011). Conclusion: The result of this study show that there are significant relationship between anthropometric, lifestyle, and high-fibre diet with the risk level of diabetes mellitus type 2.